Abbott's gambit : the 2013 Australian federal election - Johnson, Carol, 1955-; Wanna, John; Lee, Hsu-Ann (ANU Press, 2015)
Australians historically do not change governments lightly. Yet the 2013 federal election heralded a change of government-only the seventh time Australians have voted to change their national government since the Second World War. Tony Abbott, who had been Opposition Leader since 1 December 2009, became Australia's 28th Prime Minister on 18 September 2013 leading a Liberal-National Coalition with a comfortable majority in the lower house of parliament but well short of a majority in the upper house. The election result occurred after a surreal seven-and-a-half months of campaigning (actually 227 days) in which the Coalition largely held its collective nerve, while the Labor Government continued to implode through internal divisions and acrimony. To all intents and purposes the campaign was not fought principally on policy issues, but on personalities and the tarnished record of the Rudd-Gillard governments.